Effect of Hydrothermal Treatment on Dissolution and Physical Properties of Polysaccharides from Tremella fuctiformis - Yeli ZHU; Yihan WANG; Qingyun XIE; Jianwen TENG; Li HUANG; Ning XIA (Shipin gongye ke-ji)
Tremella polysaccharide is the primary component of Tremella fuciformis, and its dissolution behavior significantly influences the physical properties of the polysaccharide. In this paper, utilizing Fick's second law as a foundation, dissolution kinetic models for hot water extraction (HWE) and pressurized hot water extraction (PHWE) were developed and the relevant parameters were analyzed. Subsequently, the molecular weight of the polysaccharides and the viscosity of the extracted solution were characterized using gel permeation chromatography and a rheometer. Results showed that the polysaccharide dissolution rates of both HWE and PHWE increased with higher extraction temperatures and longer extraction times. The maximum polysaccharide dissolution rates for HWE and PHWE were determined to be 42.75% and 62.03%, respectively. The dissolution kinetics parameters, including the dissolution rate constant (k), effective diffusion coefficient (Ds), and apparent activation energy (Ea), ranged from 0.0128 to 0.0175 min−1 and 0.057 to 0.1509 min−1, 3.2532 to 4.4348 mm2·min and 14.4428~38.2676 mm2/min, 2.82 to 6.38 kJ/mol, and 19.49 to 31.43 kJ/mol. The linear coefficient of determination (R2) of the kinetic curves for both HWE and PHWE exceeded 0.87, indicating that the dissolution process adhered to Fick's second law. Additionally, the molecular weight of polysaccharides decreased with increasing extraction temperature and prolonged extraction time, the molecular weight distribution range of HWE was significantly broader than that of PHWE, and exhibited a higher apparent viscosity.